2003
DOI: 10.1289/ehp.5814
|View full text |Cite
|
Sign up to set email alerts
|

Key issues for the assessment of the allergenic potential of genetically modified foods: breakout group reports.

Abstract: On the final afternoon of the workshop "Assessment of the Allergenic Potential of Genetically Modified Foods," held 10-12 December 2001 in Chapel Hill, North Carolina, USA, speakers and participants met in breakout groups to discuss specific questions in the areas of use of human clinical data, animal models to assess food allergy, biomarkers of exposure and effect, sensitive populations, dose-response assessment, and postmarket surveillance. Each group addressed general questions regarding allergenicity of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It has also been shown that no single animal model can help in testing allergenicity responses of various GM-foods as different animal species respond differentially to the allergens, indicating that animal models should be validated (Tryphonas et al 2003). A comprehensive study addressing the allergenicity in human in response to GM-food has been discussed by Germolec et al (2003).…”
Section: Allergenicity Assessmentmentioning
confidence: 99%
“…It has also been shown that no single animal model can help in testing allergenicity responses of various GM-foods as different animal species respond differentially to the allergens, indicating that animal models should be validated (Tryphonas et al 2003). A comprehensive study addressing the allergenicity in human in response to GM-food has been discussed by Germolec et al (2003).…”
Section: Allergenicity Assessmentmentioning
confidence: 99%
“…It is essential, therefore, that every care should be taken to minimize the risks of allergic sensitization resulting from consumer exposure to food protein allergens, and to proteins contained within other products to which exposure via a relevant route might occur. As described in this article, a substantial body of literature has accumulated over the past 25 years describing the challenges posed by a need for a safety assessment approach to assess protein allergenicity, and the development of methods to address that need ( 2 , 5 12 , 14 , 69 , 80 ). The purpose of this review article has been to provide a more holistic perspective on the processes through which effective protein safety assessments can be made of potential allergenic hazards and risks associated with exposure to proteins in consumer products, with a particular focus on the application for this purpose of AllerCatPro 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that no single animal model can help in testing allergencity responses of various GM-foods as different animal species respond differentially to the allergens, indicating that animal models should be validated (Tryphonas et al 2003). A comprehensive study addressing the allergenicity in human in response to GM-food has been discussed by Germolec et al (2003, please consult for detail study).…”
Section: Allergenicity Assessmentmentioning
confidence: 99%